European identity : a historical reader (Palgrave Macmillan, 2013)
"Bringing together a wide collection of primary documents, this is an essential reader on the idea of 'Europe' from antiquity to the twentieth century. Including classic texts from antiquity alongside rare and newly translated material, this critical collection is an invaluable resource for students of European history and identity"--